Simulation and Generalized Dynamic Modeling of Metro Pantograph-Catenary System Based on Least Squares Support Vector Machine - Huang Yuping; JIANG Wei; TONG Jingquan; SHI Luxing (机车电传动)
A Generalized dynamic modeling method was proposed for pantograph-catenary system based on least squares support machine (LSSVM), and the pantograph-catenary model identification and simulation were carried out. Firstly, the ARX Hammerstein pantograph-catenary model was built after analyzing linear and nonlinear partial section of the discrete pantograph-catenary system dynamic model. Secondly the model parameters were identified based on the method of LSSVM. Finally, the pantograph-catenary contact force was modeled and predicted by the actual testing data. The simulation results showed that LSSVM-ARX Hammerstein pantographcatenary model could effectively approximate the dynamic behavior of the contact force in pantograph-catenary system with higher prediction accuracy. The proposed method was effective in train pantograph-catenary system generalized dynamic modeling.